2020
DOI: 10.1108/ijppm-05-2019-0229
|View full text |Cite
|
Sign up to set email alerts
|

Performance appraisal, justice and organizational effectiveness: a comparison between two universities

Abstract: PurposeThe purpose of this paper is to identify how the design of a performance appraisal system (PAS) affects the perceived justice of academic employees (AE) about their performance appraisal (PA) and how this is associated with organizational effectiveness in terms of organizational leadership (OL).Design/methodology/approachThe study subjects are two economic faculties of two Estonian public universities. The data for the study were collected using the PA Survey with a total of 82 AEs, OL Capability Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 103 publications
1
11
1
Order By: Relevance
“…This may be due to that head nurses perceive that their organizational goals and objectives are clearly defined and are realistic, tries to improve their working conditions, is very productive, distributes the responsibilities in reasonable way, successfully acquired human and financial resources, and they are clearly aware of the demands of their jobs and can complete tasks and achieve goals successfully. This finding supported by Kivipold and Turk (2021) (37) who reported that the mean score of organizational effectiveness was high and mentioned that the majority of workers see their organization to be high effective and place their efforts in that way.…”
Section: Discussionsupporting
confidence: 69%
“…This may be due to that head nurses perceive that their organizational goals and objectives are clearly defined and are realistic, tries to improve their working conditions, is very productive, distributes the responsibilities in reasonable way, successfully acquired human and financial resources, and they are clearly aware of the demands of their jobs and can complete tasks and achieve goals successfully. This finding supported by Kivipold and Turk (2021) (37) who reported that the mean score of organizational effectiveness was high and mentioned that the majority of workers see their organization to be high effective and place their efforts in that way.…”
Section: Discussionsupporting
confidence: 69%
“…Higher educational institutes are challenged by the requirement to constantly deliver the highest quality in academic work in their faculties and PA is used in ensuring the faculty performances always meet the required standards [42]. In the university sector, performance appraisal is identified as a tool for measuring and developing the performance of staff members of a university on an individual or team basis in terms of their work process and achievements [43]. Therefore, universities have drawn their special attention to developing performance appraisal systems related to both individual and organisational betterment and effectiveness.…”
Section: Performance Appraisal In Higher Educational Institutionsmentioning
confidence: 99%
“…Performance appraisal is one of the important steps in the process of performance management, since it is the step to examine real performance and expected performance (Cleveland et al, 2019;Kivipõld et al, 2020). The results of performance appraisal inform related people how to improve employee behaviors or substandard performance, as well as to use the results for benefits in organization management, particularly in human resource management.…”
Section: Components Of Problems In Performance Appraisalmentioning
confidence: 99%